Genomics of Environmental Salmonella: Engaging Students in the Microbiology and Bioinformatics of Foodborne Pathogens - Greenman, Noah A.; Jurgensen, Sophie K.; Holmes, Charles P.; Kapsak, Curtis J.; Davis, Raechel E.; Maza, William M.; Edemba, Desiree; Esser, Bethany A.; Hise, Selena M.; Keen, Tara N.; Larson, Hunter G.; Lockwood, Dominique J.; et al. (Frontiers in Microbiology, 2021)
We have developed and implemented an undergraduate microbiology course in which students isolate, characterize, and perform whole genome assembly and analysis of Salmonella enterica from stream sediments and poultry litter. In the development of the class and over the course of three semesters, undergraduate students collected field samples and performed enrichment and isolation techniques specific for the detection of S. enterica. Eighty-eight strains were confirmed using standard microbiological methods and PCR of the invA gene. The isolates’ genomes were Illumina-sequenced by the Center for Food Safety and Applied Nutrition at the FDA and the Virginia state public health laboratory as part of the GenomeTrakr program. Students used GalaxyTrakr and other web- and non-web-based platforms and tools to perform quality control on raw and assembled sequence data, assemble and annotate genomes, identify antimicrobial resistance and virulence genes, putative plasmids, and other mobile genetic elements. Strains with putative plasmid-borne antimicrobial resistance genes were further sequenced by students in our research lab using the Oxford Nanopore MinION™ platform. Strains of Salmonella that were isolated include common human infectious serotypes such as Typhimurium and Infantis. Over 31 of the isolates possessed resistance genes, some of which were located on large, multidrug resistance plasmids. Plasmid pHJ-38, identified in a Typhimurium isolate, is an apparently self-transmissible 183kb IncA/C2 plasmid that possesses multiple antimicrobial resistance and heavy-metal resistance genes. Plasmid pFHS-02, identified in an Infantis isolate, is an apparently self-transmissible 303kb IncF plasmid that also possesses numerous heavy-metal and antimicrobial resistance genes. Using direct and indirect measures to assess student outcomes, results indicate that course participation contributed to cognitive gains in relevant content knowledge and research skills such as field sampling, molecular techniques, and computational analysis. Furthermore, participants self-reported a deeper interest in scientific research and careers as well as psychosocial outcomes (e.g., sense of belonging, self-efficacy) commonly associated with student success and persistence in STEM. Overall, this course provided a powerful combination of field, wet lab, and computational biology experiences for students, while also providing data potentially useful in pathogen surveillance, epidemiological tracking, and for the further study of environmental reservoirs of S. enterica.